Dekontruksi Makna Pada Novel Mari Pergi Lebih Jauh Karya Ziggy Zezsyazeoviennazabrizkie Menggunakan Pendekatan Derrida - Diana, Ririn Sefty (Fakultas Sastra Universitas Muslim Indonesia, 2025)
This study aims to describe how Ziggy Zezsyazeoviennazabrizkie’s novel Mari Pergi Lebih Jauh challenges stable meanings through Jacques Derrida’s deconstructive approach. The research employs a descriptive qualitative method with textual analysis based on the principles of deconstruction, focusing on how the novel dismantles binary oppositions and reveals the absence of fixed meaning. The primary data consist of textual excerpts that reflect the play of signs, the tension between reality and imagination, and narrative contradictions that lead to the deconstruction of social and ideological structures. The findings show that the novel consistently deconstructs common views about children, powerlessness, and stereotypes surrounding parent–child relationships. Through the portrayal of complex characters, the narrative exposes the instability of meaning often overlooked by society, inviting readers to respond to the text more openly. Ziggy’s non-linear storytelling and unconventional language avoid the pursuit of a single meaning and instead open space for multiple interpretations. Ultimately, the novel encourages readers to perceive the world through a more fluid and dynamic perspective, moving away from rigid dualisms and challenging established understandings of concepts such as powerlessness, love, and social relationships.